Barleria sahyadrica, a new species of Acanthaceae from India - Prabhukumar, Konickal Mambetta; Sardesai, Milind M.; Hareesh, Vadakoot Sankaran; Thomas, Binu; George, Satheesh; Balachandran, Indira (Phytotaxa, 2019)
Barleria sahyadrica sp. nov., a new species of Barleria sect. Prionitis of the family Acanthaceae from Maharashtra region of Peninsular India is described and illustrated. A detailed description, distribution, ecology, phenology and relevant taxonomic notes are provided along with notes on the identity of B. cuspidata.